2012
DOI: 10.1364/oe.20.002452
|View full text |Cite
|
Sign up to set email alerts
|

Model calculations for enhanced fluorescence in photonic crystal phosphor

Abstract: We propose a novel photonic structure, based on the photonic crystal (PC) effect, which simulations show results in an improved fluorescence efficiency from embedded phosphor. To be specific, the phosphor pumping efficiency can be significantly improved by tuning the pump photon energy to a photonic band-edge (PBE) of the PC phosphor. We have confirmed this theoretically by calculating optical properties of one-dimensional PC phosphor structures using the transfer-matrix method and plane-wave expansion method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…(d) Reflectance spectrum of a 1D PhC comprised of 30 unit cells showing the electric field intensity profiles for four selected wavelengths within and outside the PBG. Reproduced with permission . Copyright 2012, Optical Society of America.…”
Section: Polymer‐based Photonic Structuresmentioning
confidence: 99%
“…(d) Reflectance spectrum of a 1D PhC comprised of 30 unit cells showing the electric field intensity profiles for four selected wavelengths within and outside the PBG. Reproduced with permission . Copyright 2012, Optical Society of America.…”
Section: Polymer‐based Photonic Structuresmentioning
confidence: 99%
“…Mainstream phosphor development—to improve color conversion efficiency or to tune absorption/emission bands—has so far been predominantly materials‐oriented . Quite recently, the authors' group proposed and demonstrated a paradigm‐shifting concept in phosphor research, called photonic crystal (PhC) phosphors . The basic idea behind PhC phosphors is to structurally engineer phosphor materials into periodic PhCs—with the associated photonic band‐edge (PBE) modes tuned to the phosphor excitation wavelength—to induce an enhancement in phosphor excitation efficiency (and therefore color conversion efficiency).…”
mentioning
confidence: 99%
“…The basic idea behind PhC phosphors is to structurally engineer phosphor materials into periodic PhCs—with the associated photonic band‐edge (PBE) modes tuned to the phosphor excitation wavelength—to induce an enhancement in phosphor excitation efficiency (and therefore color conversion efficiency). To demonstrate the viability and applicability of the technology, we stacked two batches of the PhC phosphor films emitting in red and green on top of a blue LED chip to efficiently and economically produce high‐quality white light 4d…”
mentioning
confidence: 99%
See 2 more Smart Citations